Trends in Rice Production and Varieties in the Everglades Agricultural Area - Jehangir H. Bhadha; Luigi Trotta; Matthew VanWeelden (EDIS)
Rice production in the Everglades Agriculture Area (EAA) of Florida dates back nearly seven decades. For a brief period in the 1950s about 2,000 acres of rice was grown in the EAA. Rice was reintroduced in the EAA in 1977 after it was demonstrated that rice could be successfully incorporated into the sugarcane production cycle during the fallow period. This 3-page fact sheet provides a history of rice production in Florida and information about rice varieties grown in Florida. Written by Jehangir H. Bhadha, Luigi Trotta, and Matthew VanWeelden, and published by the Soil and Water Sciences Department, May 2016.